Resolution of the civil service collective bargaining dilemma - Williams, Richard C. (1994)
The conflict between the parallel rule-making systems of civil service and collective bargaining has existed in local and state employment since collective bargaining emerged among large numbers of these employees. This article traces the development of a number of legal theories tried by courts in a number of key states to resolve this dilemma. It concludes with a more detailed analysis of the evolution of court opinion in Ohio resulting from the imposition of its 1983 Public Employee Collective Bargaining Act Lessons for drafting future legislation in other states are abstracted from this analysis. - Reproduced
Keywords: Civil service - United States; Civil service